Suatu Kegentingan Memaksa Menjadikan Peraturan Pemerintah Pengganti Undang-Undang Menjadi Undang-Undang - Iskandar Iskandar (JOURNAL of LEGAL RESEARCH, 2022)
The State of Indonesia is a legal state that tries to keep things in order and make things clear for the people who work for the government. People and the government should always use the law as a guide when they do things in the name of the country or state. The Constitution gives the President, who is in charge of the government, the power to make a rule called a "Government Regulation in Lieu of a Law." This rule is meant to make sure that the safety of the state can be taken care of by the government in an emergency so that the government can act quickly and appropriately. Regulations made by the government instead of law are rules that are at the same level as the law, made in a time of crisis, and formed by the President. They do the same thing as the law. The President can make rules for the government instead of law when there is a "compelling need." This means that Perppu must be based on Pancasila and Indonesia's constitution from 1945. It must also be based on state laws and basic laws in-laws and regulations, and it must also be the source of laws and regulations, as well. The one on the bottom. Even though the level and degree of the law are the same, there are a lot of differences between the two types of legislation, including who made it, how it was made, and when it was made.